Cell Wall Polysaccharide Composition of Grafted ‘Liberty’ Watermelon With Reduced Incidence of Hollow Heart Defect - Trandel, Marlee A.; Johanningsmeier, Suzanne; Schultheis, Jonathan; Gunter, Chris; Perkins-Veazie, Penelope (Frontiers in Plant Science, 2021)
Grafting watermelon scions to interspecific squash hybrids has been found to increase fruit firmness. Triploid (seedless) watermelon are prone to hollow heart (HH), an internal fruit disorder characterized by a crack in the placental tissue expanding to a cavity. Although watermelon with lower tissue firmness tend to have a higher HH incidence, associated differences in cell wall polysaccharide composition are unknown. Grafting ‘Liberty’ watermelon to ‘Carnivor’ (interspecific hybrid rootstock, C. moschata x C. maxima) reduced HH 39% and increased tissue firmness by 3 N. Fruit with and without severe HH from both grafted and non-grafted plants were analyzed to determine differences in cell wall polysaccharides associated with grafting and HH. Alcohol insoluble residues (AIR) were sequentially extracted from placental tissue to yield water soluble (WSF), carbonate soluble (CSF), alkali soluble (ASF) or unextractable (UNX) pectic fractions. The CSF was lower in fruit with HH (24.5%) compared to those without HH (27.1%). AIRs were also reduced, hydrolyzed, and acetylated for GC-MS analysis of monosaccharide composition, and a portion of each AIR was methylated prior to hydrolysis and acetylation to produce partially methylated alditol acetates for polysaccharide linkage assembly. No differences in degree of methylation or galacturonic and glucuronic acid concentrations were found. Glucose and galactose were in highest abundance at 75.9 and 82.4 g·mg-1 AIR, respectively, followed by xylose and arabinose (29.3 and 22.0 g·mg-1). Mannose was higher in fruit with HH (p < 0.05) and xylose was highest in fruit from grafted plants (p < 0.05). Mannose is primarily found in heteromannan and rhamnogalacturonan I side chains, while xylose is found in xylogalacturonan or heteroxylan. In watermelon, 34 carbohydrate linkages were identified with galactose, glucose and arabinose linkages in highest abundance. This represents the most comprehensive polysaccharide linkage analysis to date for watermelon, including the identification of several new linkages. However, total pectin and cell wall composition data could not explain the increased tissue firmness observed in fruit from grafted plants. Nonetheless, grafting onto the interspecific hybrid rootstock decreased the incidence of HH and can be a useful method for growers using HH susceptible cultivars.